Hypercholesterolemia-induced LXR signaling in smooth muscle cells contributes to vascular lesion remodeling and visceral function - Hanming Zhang; Diego Sáenz de Urturi; Pablo Fernández-Tussy; Yan Huang; Daniel G. Jovin; Xinbo Zhang; Shushu Huang; Monkol Lek; Jonatas da Silva Catarino; Magdalena Sternak; Kathryn M. Citrin; Fillip K. Swirski; et al. (Proceedings of the National Academy of Sciences, 2025)
Vascular smooth muscle cells (VSMC) are the most abundant cell type in the artery’s media layer and regulate vascular tone and lesion remodeling during atherogenesis. Like monocyte-derived macrophages, VSMCs accumulate excess lipids and contribute to the total intimal foam cell population in human coronary plaques and mouse aortic atheroma. While there are extensive studies characterizing the contribution of lipid metabolism in macrophage immunometabolic responses in atherosclerotic plaques, the role of VSMC lipid metabolism in regulating vascular function and lesion remodeling in vivo remains poorly understood. Here, we report that the liver X receptor (LXR) signaling pathway in VSMC is continuously activated during atherogenesis. Notably, we found that LXR deficiency in SMCs under hypercholesterolemic conditions influenced lesion remodeling by altering the fate of dedifferentiated SMCs and promoting the accumulation of VSMC-derived transitional cells. This phenotypic switching was accompanied by reduced indices of plaque stability, characterized by a larger necrotic core area and reduced fibrous cap thickness. Moreover, SMC-specific LXR deficiency impaired vascular function and caused visceral myopathy characterized by maladaptive bladder remodeling and gut lipid malabsorption. Mechanistically, we found that the expression of several genes involved in cholesterol efflux and FA synthesis including Abca1 , Srebf1 , Scd1 , Scd2 , Acsl3, and Mid1ip1 was downregulated in mice lacking LXRαβ in SMCs, likely contributing to the phenotypic switching of VSMC in the atherosclerotic lesions.